Metallic Intrapulmonary Foreign Body by Playful Accident in A Child - Marème Soda Mbaye; Momar Sokhna Diop; Souleymane Diatta; Pape Ousmane; Amadou Gabriel Ciss; Assane Ndiaye (Journal of Clinical Case Reports and Images, 2022)
Intrathoracic foreign bodies secondary to penetrating wounds are rare in children. We report the observation of a 10-year-old patient who presented an intrapulmonary metallic foreign body following a playful accident. Its migratory aspect, highlighted by imaging, required urgent extraction which was performed by thoracotomy, with good clinical outcome. The interest of the question lies in the circumstances of the incident, the type of foreign body and the terrain.
Keywords: intrathoracic foreign body